Pengaruh Strategi Reading Aloud terhadap Kemampuan Membaca Al-Qur’an Siswa Madrasah Ibtidaiyah - Anggraini , Kiky Chandra Silvia; Fathiyatussholihah, Fathiyatussholihah (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
One of the effects of the lack of fluency and pronunciation of the letters of the Al-Qur’an is the low ability to read. The solution to the low ability to read the Al-Qur'an is to apply the reading-aloud strategy. This study aims to determine the application of reading aloud and the effect of the reading aloud strategy on the ability to read the Al-Qur'an in learning Al-Qur'an Hadith. This research applied a quantitative method of Quasi Experiment type with one group pretest post-test Design. The instrument used is a performance sheet in the form of a reading ability test, which is analyzed with the SPSS test in the form of Paired Sample T-Tes. Based on the study results, the pretest results were lower than the post-test. Based on data analysis to test the research hypothesis, it is known that the significance value is 0.000